Referential Practice : Language and Lived Space among the Maya - Hanks, William F. (University of Chicago Press, 1990)
Referential Practice is an anthropological study of language use in a contemporary Maya community. It examines the routine conversational practices in which Maya speakers make reference to themselves and to each other, to their immediate contexts, and to their world. Drawing on extensive fieldwork in Oxkutzcab, Yucatán, William F. Hanks develops a sociocultural approach to reference in natural languages. The core of this approach lies in treating speech as a social engagement and reference as a practice through which actors orient themselves in the world. The conceptual framework derives from cultural anthropology, linguistic pragmatics, interpretive sociology, and cognitive semantics. As his central case, Hanks undertakes a comprehensive analysis of deixis—linguistic forms that fix reference in context, such as English I, you, this, that, here, and there. He shows that Maya deixis is a basic cultural construct linking language with body space, domestic space, agricultural and ritual practices, and other fields of social activity. Using this as a guide to ethnographic description, he discovers striking regularities in person reference and modes of participation, the role of perception in reference, and varieties of spatial orientation, including locative deixis. Traditionally considered a marginal area in linguistics and virtually untouched in the ethnographic literature, the study of referential deixis becomes in Hanks’s treatment an innovative and revealing methodology. Referential Practice is the first full-length study of actual deictic use in a non-Western language, the first in-depth study of speech practice in Yucatec Maya culture, and the first detailed account of the relation between routine conversation, embodiment, and ritual discourse. -- Présentation de l'éditeur.